SIKAP PROFESIONAL DAN ETOS KERJA GURU DALAM PENINGKATAN EFEKTIVITAS KERJA - N, Asri (Universitas Islam Negeri Alauddin Makassar, 2018)
The professional attitude of the teacher is the attitude of a teacher in carrying out his work which includes expertise, skills and skills that meet certain quality standards or norms and requires teacher professional education. In this case a professional teacher is required with a number of minimum requirements, among others: having the quality of adequate professional education, having scientific competence in accordance with the field he occupies, having good communication skills with his students, having a creative and productive spirit, having a work ethic and high commitment to the profession, and always carry out self-development continuously (countinuous improvement) through professional organizations, the internet, books, seminars and the like. The teacher as a professional educator has a good image in the community if he can show the community that he deserves to be a role model or example of the surrounding community. The community will see how the teacher's attitudes and actions are done everyday, is there really something to follow or not? How do teachers improve their services, improve their knowledge, give direction and encouragement to their students? How do teachers dress, talk and how to get along well with students, friends and community members? All of that became the public's attention point.